PENGARUH KINERJA KARYAWAN TERHADAP KUALITAS PELAYANAN NASABAH PADA PT. PEGADAIAN CABANG TOBELO, KABUPATEN HALMAHERA UTARA - Vrisca Bangoro, Yulans; Kaiyeli, Nasrula (CV. Anugerah Duta Perdana, 2023)
The aim of this research is to examine the influence of employee performance on service quality. This research uses an associative approach, using primary data through questionnaires. Respondents in this research were customers of PT. Pawnshop Tobelo Branch, North Halmahera Regency. The population used was 50 customers. saturated side technique where all members of the population were sampled in this research. The data collection technique used was a questionnaire. The data analysis techniques used are validity test, reliability test, simple linear regression, correlation coefficient, determination test and t test. Data testing was carried out with the help of the SPSS program. Based on the results of the analysis, it shows that employee performance has a positive and significant effect on service quality. The test results show that the employee performance variable value is sig 0.000 <0.05 and the ttable value is 1.677 and tcount is 7.995. The value of the coefficient of determination shows that employee performance is 56.2% while the remaining is 43.8%.